Reproducibility of hippocampal atrophy rates measured with manual, FreeSurfer, AdaBoost, FSL/FIRST and the MAPS-HBSI methods in Alzheimer's disease. (30th June 2016) - Cover, Keith S.; van Schijndel, Ronald A.; Versteeg, Adriaan; Leung, Kelvin K.; Mulder, Emma R.; Jong, Remko A.; Visser, Peter J.; Redolfi, Alberto; Revillard, Jerome; Grenier, Baptiste; Manset, David; Damangir, Soheil; et al.
Abstract: The purpose of this study is to assess the reproducibility of hippocampal atrophy rate measurements of commonly used fully-automated algorithms in Alzheimer disease (AD). The reproducibility of hippocampal atrophy rate for FSL/FIRST, AdaBoost, FreeSurfer, MAPS independently and MAPS combined with the boundary shift integral (MAPS-HBSI) were calculated. Back-to-back (BTB) 3D T1-weighted MPRAGE MRI from the Alzheimer's Disease Neuroimaging Initiative (ADNI1) study at baseline and year one were used. Analysis on 3 groups of subjects was performed – 562 subjects at 1.5 T, a 75 subject group that also had manual segmentation and 111 subjects at 3 T. A simple and novel statistical test based on the binomial distribution was used that handled outlying data points robustly. Median hippocampal atrophy rates were −1.1%/year for healthy controls, −3.0%/year for mildly cognitively impaired and −5.1%/year for AD subjects. The best reproducibility was observed for MAPS-HBSI (1.3%), while the other methods tested had reproducibilities at least 50% higher at 1.5 T and 3 T which was statistically significant. For a clinical trial, MAPS-HBSI should require less than half the subjects of the other methods tested. All methods had good accuracy versus manual segmentation. The MAPS-HBSI method has substantially better reproducibility than the other methods considered. Highlights: Compared the reproducibility of methods for measuring hippocampal atrophy rates. Compared FreeSurfer, FSL/FIRST, MAPS-HBSI, AdaBoost and manual. Back-to-back MPRAGEs at baseline and year one for N=562 ADNI1 1.5 T subjects. Used a novel but simple statistical test that is robust to outlying data points. MAPS-HBSI should require half the subjects in a clinical trial than others tested.